PENGARUH PEMBERITAAN MEDIA MASSA PADA MOTIVASI OLAHRAGAWAN - Setyawati, Heny (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2017)
Sports performance is influenced by the existence of positive and negative expectations on a particular thing. Positive expectations will have a positive impact on appearance, as well as negative expectations will have a negative impact on appearance. Positive Expectations on Sportsmen are influenced by their motivation in exercising. Great motivation will result in maximum performance. One external factor that could affect motivation to the athlete is coverage in the mass media. The purpose of this study is to determine the influence of mass media coverage on the motivation of athletes. The research used qualitative design with phenomenology approach, that is reducing psychological experience of sportsman related to news in mass media. The method used to obtain data by conducting interviews, observation and documentation. The influence of mass media coverage on athletes, especially in improving degree in execution of tasks. Positively perceived news in the mass media build motivates the sportsman to try to get better. They become motivated and more enthusiastic in practicing and competing. The condition implies that when the sportsman appears to be news material in the mass media can positively increase hisspirits both in practice and in the face of the game. On the other hand the negative news in the mass media did not make them pull away or down. Instead of negative news there is actually a motivation for them to show that they can be more achievers again and not as reported. It is also a correction for them to improve themselves. Suggestions that can be drawn from the conclusions and implications of this study are as follows: For athletes, can be a reference for how to process information appropriately, to develop motivation. For the media, to help the athlete through the construction of news coverage in the mass media to build athletes motivation.